Risk Factors in Obstetric Hysterectomy in a Second Level Hospital in Mexico - Malagon, Genaro Vega; Garcia, Luis Nelson Bautista; Lugo, Silvia Barrios; Malagón, Jesús Vega; Santos, Alma Becerril; Morales, Javier Avila (European Scientific Journal, ESJ, 2017)
Objective - To determine the risk factors for obstetric hysterectomy in a second level hospital in Mexico. Methodology.- Epidemiological study of cases and controls from January 2014 to December 2016 at the Child and Women Specialties Hospital of Querétaro. The cases were 56 women with obstetric hysterectomy, controls, 56 women without the procedure, sampling was random simple probabilistic in both groups, analyzed: age, schooling, parity, route of abortion, antecedent of previous cesarean sections, Uterine hypotonia, placental accretismo. For the analysis, descriptive and inferential statistics were used with chi2 test, student t, odds ratio (O.R.), and I.C. 95%, and a value of p <0.05). Results.-The mean age of the group of cases was 30.3 years (D.E. of 7,139) and the controls of 25.08 (D.E. of 5.979) with a p: <0.05. The factors that showed statistically significant difference (p: <0.05) were: Placental acretism (O.R., 126.17); Hypotonia or uterine atony (O.R., 8.22); Multiparity of 3 or more pregnancies (O.R., 5.11); Age of 28 years or more (O.R. of 4.86), placenta previa (O.R. of 3.11); Antecedent of two previous C-sections (O.R. of 2.77); Route of interruption of pregnancy by cesarean section (O.R. of 2.75) and cesarean antecedent (O.R. of 2.55). There was one maternal death in the case group. Conclusions: Obstetric hysterectomy is an emergency surgery, so the risk factors for this complication must be identified during prenatal care.